Leptin concentration and risk of coronary heart disease and stroke: A systematic review and meta-analysis. - Han Yang; Wenzhi Guo; Jie Li; Shengli Cao; Jiakai Zhang; Jie Pan; Zhihui Wang; Peihao Wen; Xiaoyi Shi; Shuijun Zhang (PLoS ONE)
Background and purpose Although high leptin concentration has been shown to be correlated with established vascular risk factors, epidemiologic studies have reported inconclusive results on the association between leptin and cardiovascular diseases (CVD). Therefore, a meta-analysis was performed to evaluate this issue. Methods We searched Pubmed, Embase, and the Cochrane Library from their inception to Jan 2016 for both case-control and cohort studies that assessed leptin concentration and CVD risk. Reports with odds ratio (OR), risk ratio (RR) and corresponding 95% confidence intervals (CI) were considered. The data were extracted by two investigators independently. Results A total of 13 epidemiologic studies totaling 4257 CVD patients and 26710 controls were included. A significant inverse association was shown between leptin and coronary heart disease (CHD), with an overall OR of 1.16 (95% CI: 1.02-1.32), but not for stroke (OR = 1.21, 95% CI 0.98-1.48) under sociodemographic adjustment. Further adjustment for additional cardiovascular risk factors resulted in ORs of 1.16 (95% CI 0.97-1.40) for CHD and 1.10 (95% CI 0.89-1.35) for stroke. The findings remained when analyses were restricted to high-quality studies and indicated OR estimates of 1.07 (95% CI 0.96-1.19) for CHD and 0.98 (95% CI 0.76-1.25) for stroke. In a subgroup meta-analysis, a high leptin level was not independently associated with CHD in both females (OR = 1.03, 95% CI 0.86-1.23) and males (OR = 1.09, 95% CI 0.95-1.26) or with stroke in both females (OR = 1.13, 95% CI 0.87-1.47) and males (OR = 0.80, 95% CI 0.59-1.09). There was no significant publication bias as suggested by Egger test outcomes. Conclusions Our findings indicate that high leptin levels may not be associated with risks of CHD and stroke. Further large, well-designed prospective cohort studies are needed to fully evaluate the role of leptin on the risk of CVD.